AKULTURASI BUDAYA PADA ARSITEKTUR BANGUNAN DI PALEMBANG - Syafitri, Adesta; Ariesta, Adinda Dwi; Maryamah, Maryamah; Berlianna, Romsiah (STKIP PGRI Situbondo, 2024)
The existence of different cultures gives birth to different architectural styles. When two or more cultures meet, cultural acculturation occurs in the architecture of the building, or in several architectural elements, or in the entire building. Acculturation is a social process that arises when a group of people from a culture combines elements of a foreign culture, so that they can be accepted and processed into their own culture without causing a loss of their original cultural personality.One area in Indonesia that can be said to have a long history and culture is the city of Palembang. Palembang was famous from the time of the Sriwijaya Kingdom to the Palembang Darussalam Sultanate and was synonymous with a business economy that used sea routes. It is not surprising that the creation of cultural acculturation is a natural thing.Examples of the historical heritage of the city of Palembang which experienced acculturation or architectural mixing can be seen from houses of worship and residential buildings, namely the Palembang Grand Mosque (Sultan Mahmud Badaruddin Jayo Wikramo Grand Mosque), the Cheng Ho Mosque (Al Islam Muhammad Cheng Hoo Mosque Sriwijaya Palembang), and the House Limas (traditional house of South Sumatra). The method used in this research is a qualitative method with a descriptive approach using library research. Keywords : acculturation, culture, architecture, Palembang